What is being written about Education and Pedagogy in Colombia? - León Palencia, Ana Cristina; Gil Pinto, Yeidy Alexandra; Cárdenas Vera, Erica Yuliana; García Zúñiga, María de los Ángeles; López Reyes, Greizzy Eliana (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article presents a review of the journals Pedagogía y Saberes (UPN) and Praxis & Saber (UPTC) on the basis of an analysis of concepts. The question regarding what has been done in the area of education and pedagogy in Colombia during the last decades is addressed at three different stages. Firstly, a reflection is made on the ways in which the epistemological status of pedagogy has been discussed and on the possibility of using the term field as a method for easing tensions created in the eighties. In particular, the conceptual field of pedagogy concept is widened and the methodological aspects of the study are briefly described. Secondly, some key concepts articulating the debate such as: education, pedagogy, training, educator (teacher/educationist), school, discipline, didactics, knowledge, or philosophy are presented in accordance with each journal by making reference to the tensions that characterize them and some strides. Lastly, three points are highlighted: the adjectivization of the concepts, the demands for conceptualization and the need to make a clear distinction between the concepts.